Identity Dynamics in Collegiate Olympic Athletes Post-Tokyo 2020: A Pre-Post Study - Grace Kazmierski-Davie; Khalid Ballouli (University of Kansas Libraries, 2024)
This study employs a pre-post survey design, engaging a purposive-convenience sample of 94 U.S. college athletes who participated in the Tokyo 2020 Summer Olympics across eight sports and 22 countries. Utilizing validated scales, participants' group, national, and athletic identities were measured weeks before and after the event. Paired sample t-tests and a repeated measures multivariate analysis of variance were utilized to understand the effects of time and demographic variables on these identities. Results revealed that after competing in the Tokyo 2020 Olympics, college athletes exhibited a significant decrease in their group identity and a significant increase in their national identity, while their athletic identity remained relatively unchanged. The results were qualified by student status interactions such that international students showed a significant decrease in group identity and a significant increase in national identity after competing in Tokyo 2020, with no significant changes observed in these identities for domestic students. The results illuminate a complex process of identity negotiation experienced by collegiate Olympic athletes that transition between Olympic and college sport environments. This study contributes to sport management literature by offering nuanced insights into the dynamics of role-switching, urging stakeholders to utilize these findings to enhance the experiences of college athletes.